Atomic Structure and Chemical Composition of Planar Fault Structures in Co-Base Superalloys - Lenz, Malte; Wu, Mingjian; He, Junyang; Makineni, Surendra K.; Gault, Baptiste; Raabe, Dierk; Neumeier, Steffen; Spiecker, Erdmann (Minerals, Metals and Materials Series, 2020)
We report atomic structures and chemical compositions of defects associated to planar faults in a creep deformed Co-base superalloy and discuss their formation and contribution to plastic deformation. The multinary single crystalline Co-base superalloy was creep deformed under tension along [ 001 ] -direction at 850 °C and 400 MPa. The creep microstructure comprises a high density of planar defects. Solute segregation to superlattice intrinsic stacking faults (SISF) is characterized via EDXS analysis of a statistically relevant number of faults and compared at different creep stages. The amount of solute segregation shows negligible difference at different creep stages indicating that segregation directly occurs during planar fault formation and does not significantly evolve afterward. Based on the observation and analysis of Frank partial dislocations with a/3⟨111⟩ Burgers vectors terminating SISF, we discuss a new route to SISF formation via dislocation climb. Additionally, two more complex fault structures are analyzed, and potential formation mechanisms are discussed. The first of these structures is a terminating end of an SISF where an a/3⟨112⟩ partial dislocation splits up into two closely spaced a/6⟨112⟩ partials separated by an SESF. The second structure consists of two parallel SISFs connected by an anti-phase boundary (APB). All deformation mechanisms described in this study show an involvement of solute segregation directly affecting formation and propagation of creep defects by changing planar fault energies and chemical environments of dislocations. Solute segregation is therefore expected to be a key to future alloy design by enabling control of creep deformation mechanisms in specific temperature and stress regimes.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Co-base superalloy; Creep; Frank dislocation; Segregation; Stacking faults